KETERAMPILAN MENGANYAM SPON EVA UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK TUNAGRAHITA SEDANG DI SLB SUKAPURA BANDUNG - SEPTIANI, DWITHYA (2014)
Abstract : The purpose of this research was to acquire information and facts about the effectiveness of weaving sponge of eva to improve fine motor skills, children are mentally retarded. Subject in this research was on students are mentally retarded (BW dan MR), the grade in III elementary school at Special School of Sukapura. Subject have low cognitive abilities and because of that students have problems in fine motor skills. Necessary training and attractive to attract students, so it can be improve the fine motor skills of students. Workout weave sponge of eva have crowded material and corolfull, its can help attract the attention of students. This study uses experimental research, and Single Subject Research approach, design of the A-B-A. Based on these findings the results at this research , weaving sponge of eva can improve fine motor skills to mentally retarded students (BW and MR). This is proved by the increase in the mean levels at each phase of the first phase is baseline-1 then the intervention and baseline-2 at BW and MR students.